Migrant fertility in Germany and the Eastern enlargement of the EU - Katharina Wolf; Michaela Kreyenfeld (Deutsches Institut für Wirtschaftsforschung (DIW), 2020)
This paper uses data from the Migrant Samples of the German Socio-Economic Panel to study the fertility behaviour of women who migrated to Germany between 1990 and 2015. Special emphasis is placed on the large groups of migrants who have moved to Germany from Central and Eastern European (CEE) countries since the 1990s. We find that CEE migrants had higher first birth, but much lower second birth rates than migrants from other European countries. Different from the pattern of African and Middle Eastern migrants, we do not find a spike in first birth rates after migration. We also examined differences within the group of migrants from CEE-countries. In particular, we examined whether Ethnic German migrants differed from migrants who moved as third country national or those who moved after their country became EU-members with the right to free movement of labor. We find that CEE-migrants who moved when their country was a member state of the European Union display strongly reduced first birth rates.
Keywords: 330; Migranten; Osteuropäer; Fertilität; Deutschland